Analisis Konseptual Mengenai Mental Hygiene dalam Perspektif Psikologi dan Islam Menurut Syamsu Yusuf - Komaruddin Komaruddin; Zhila Jannati; Herwantoro Herwantoro (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
Mental hygiene is the efforts made to achieve mental health (mental health). This study aims to determine the concept of mental hygiene in a psychological and Islamic perspective according to Syamsu Yusuf. This study uses library research methods, by analyzing the main book, namely the book